Integrating genetic maps in bambara groundnut [Vigna subterranea (L) Verdc.] and their syntenic relationships among closely related legumes - Ho, Wai Kuan; Chai, Hui Hui; Kendabie, Presidor; Ahmad, Nariman Salih; Jani, Jaeyres; Massawe, Festo; Kilian, Andrzej; Mayes, Sean (BioMed Central, 2017)
Background